Beyond Custody Versus Care: Understanding the Ethical Dilemmas of Prison Officers in Belgium - van Dijk, Milou (European journal on criminal policy and research, 2023)
It is often argued that the work of prison officers involves many value tensions. However, existing conceptualizations seem to be insufficient to address the broad range of such tensions. For example, the tensions are often depicted as binary (‘custody versus care’), operationalizations of the values are inconsistent, and tensions are not always linked to specific difficult situations for prison officers. While building upon existing work, this article looks at these value tensions through a different lens. It reconceptualizes them as ethical dilemmas and uses Moral Foundations Theory to describe the different values involved in those ethical dilemmas. Using interview data collected in a Belgian prison, the article shows how ethical dilemmas are more complex than is often assumed, and that prison officers draw upon a multitude of values to deal with them.